Self-Reliance through Innovation and Entrepreneurship Competency of Technical/Engineering Polytechnic Students in Nigeria - Shirka Kassam Jwasshaka; Nor Fadila Mohd Amin; Gimba Dogara (Jurnal Pendidikan Teknologi dan Kejuruan, 2018)
The study aimed at assessing the adequacy of innovative and entrepreneurial competency of Technical /Engineering students of Plateau State Polytechnic for self-reliance. It was primarily sought to determine whether they were opinions of final year Technical and engineering students.  A descriptive survey design was adopted where 120 respondents were randomly selected from the School of Technical Education and Engineering. 45 items structured questionnaire was used for the collection of data related to innovation and entrepreneurship competency in order to be self-reliant. The instrument was validated by three experts; two from Plateau State Polytechnic and one from the private sector. Data were analyzed using the descriptive statistic to determine the mean and the standard deviation of respondents. The findings of the study revealed that final year students need innovative and entrepreneurial competencies for self-reliant after graduation. The study also showed that the training provided is not sufficient for the prospective graduates to be able to face the challenges in the myths of job scarcity. Recommendations based on the findings of the study was highlighted which includes the need for a complete overhauling of Technology Education curriculum to reflect the current realities.capable of setting up small-scale business after graduation. Three research questions were formulated to seek